Expression of PTX3, GHR and GDF9 genes in cumulus cells and oocytes in relation to developmental competence of Bos indicus - DEV, H; DUTTA, D J; BORAH, P; RAJ, H; HUSSAIN, I; SAIKIA, J (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to evaluate the level of expression (mRNA) of specific developmental marker genes, viz. Growth Differentiation Factor 9 (GDF9), Growth Hormone Receptor (GHR) and Pentraxin 3 (PTX3) in bovine cumulus cells and oocytes in relation to in vitro developmental competence. Good quality Cumulus- Oocytes- Complexes (COCs) were selected for in vitro maturation and fertilization. The mean percentage of in vitro fertilization performance was 59.84 ± 4.28. The relative quantification values of GDF9 were 2.38, 98.13, 1 and 132.58; GHR were 4.31, 1.47, 1 and 43.58; PTX3 were 0.28, 0, 1 and 0.5 in immature cumulus cells, immature oocyte, mature cumulus cells and mature oocyte respectively when compared to the reference control. The expression of GDF9 gene was found to be up-regulated in oocytes compared to cumulus cells. The expression pattern of GDF9 was relatively more in in vitro matured oocytes compared to cumulus groups. The expression of GHR gene was up-regulated in oocytes. The relative abundance of PTX3 was slightly up-regulated in mature cumulus cells as compared to immature counterparts. Thus, GDF9 and GHR genes could be considered as embryonic developmental markers for bovine oocytes, while PTX3 gene for bovine cumulus cells.